Comparative Study of Natural Polymers and Titanium as a Medical Implant in Terms of Safety - Filbert Nicklaus Gunawan; Agus Limanto (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Titanium has been utilized as an implant material because of its mechanical properties, corrosion resistance, and biocompatibility. However, there are some issues in using titanium for medical implants such as particle release that could be toxic to the native environment. Therefore, it is necessary to find safer substitute materials such as natural polymers, which are found to be great in biocompatibility and less toxic. In this paper, we discussed the safety characteristics such as biocompatibility, biodegradability, and mechanical properties for both materials. The source of information was gathered through online databases, PubMed, using keywords such as titanium, 3D bioprinting, and implant, and further screened with biocompatibility, mechanical characteristics, gelatin, fibrin, cellulose, alginate, agarose, silk, in-vitro and in-vivo. Journal publications that did not discuss biocompatibility, biodegradability, mechanical qualities, could not be opened, and were not research articles were excluded. The 9 journals were selected based on the inclusion, title, and abstract. It can be concluded that natural polymers could be a titanium alternative based on its safety characteristics. Further studies are required to do more research about their safety to be used as medical implant material.